Personalized human emotion classification using genetic algorithm - Mohd Rizon; Hazry, Desa; Karthigayan, M.; Nagarajan, Ramachandran; Alajlan, N.; Sazali, Yaacob, Prof. Dr.; Nor Azmi, Johari; Ina Suryani, Ab Rahim (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/